3D models related to the publication: New information on the braincase and endocranial morphology of the Late Triassic neotheropod Zupaysaurus rougieri using Computed Tomography data - Paulina Carabajal, Ariana (2019)
The present 3D Dataset contains the 3D models analyzed in the following publication: Paulina-Carabajal, A., Ezcurra, M., Novas, F., 2019. New information on the braincase and endocranial morphology of the Late Triassic neotheropod Zupaysaurus rougieri using Computed Tomography data.